2008
DOI: 10.1002/da.20350
|View full text |Cite
|
Sign up to set email alerts
|

Risk of emotional disorder in offspring of depressed parents: gender differences in the effect of a second emotionally affected parent

Abstract: In offspring of depressed parents a second parent with emotional problems is likely to increase risk of emotional disorder. This effect may however differ between sons and daughters and between offspring of depressed fathers and offspring of depressed mothers. In adolescent and young-adult offspring of parents with major depressive disorder, this study examined the effects of a second affected parent, offspring gender, gender of the depressed parent and their interactions on risk of depression and anxiety diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…While some studies have found evidence to suggest that maternal psychopathology has a greater impact on offspring risk than paternal psychopathology (Johnson et al 2006; Landman-Peeters et al 2008; Low et al 2012; Merikangas et al 1988), other studies have found no evidence that the effect is different for mothers and fathers (Dean et al 2010; Kendler et al 1997; Lieb et al . 2002; Weissman et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found evidence to suggest that maternal psychopathology has a greater impact on offspring risk than paternal psychopathology (Johnson et al 2006; Landman-Peeters et al 2008; Low et al 2012; Merikangas et al 1988), other studies have found no evidence that the effect is different for mothers and fathers (Dean et al 2010; Kendler et al 1997; Lieb et al . 2002; Weissman et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…2002; Weissman et al 1987). Similarly, there is disagreement in the literature regarding the effect of offspring gender: several studies found evidence that parental psychopathology has a greater impact on depression risk for girls (Klein et al 1988; Landman-Peeters et al 2008; Morris et al 2014), while others found no evidence of gender differences (Ohannessian et al 2005). In this study, we found a significant interaction between parental history and offspring gender, but in the opposite direction from previous studies: parental history of affective disorders had a greater effect on males than on females.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a healthy parent was not explained by better SES in the household. Regarding other potential mechanisms, parent–child conflict has been reported to mediate the association between maternal14 and paternal2 depressive symptoms and psychopathology in offspring. Thus, normal interaction with one healthy parent may protect children with one parent on antidepressants and one healthy parent.…”
Section: Discussionmentioning
confidence: 99%
“…In 3-year-old children, paternal depression or anxiety was not as influential as maternal psychiatric morbidity in predicting emotional and behavioural problems 3. Another study found both paternal and maternal depression to additively increase daughters’ risk of emotional disorder, but sons’ risk only increased with maternal depression 4. Adoption studies found stronger support for adoptive mother's than adoptive father's effect on symptoms and morbidity in offspring 5 6…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Lewis and colleagues, findings show that hostility in mother-daughter relationships increased the risk for depression in the daughters only (Lewis et al 2014). Hartman et al (2008) looked at the effect of parental depression on the male and female offspring’s presence of depression or anxiety, and whether the likelihood of the offspring having depression or anxiety varied by gender and the number of affected parents. Of the four groups, daughters who had affected mothers were at the highest risk for depression and anxiety.…”
mentioning
confidence: 99%